Wheelchair tennis player movement speed: Differences in movement, with and without a racket - Sánchez-Pay, A.; Sanz-Rivas, D. (Coaching and Sport Science Review, 2018)
This study attempted to measure the capacity of wheelchair tennis players to accelerate and change directions, as well as investigate the differences with regard to the level of the athlete, either using the racket or not using the racket, when moving. 9 international players participated in this study. We measured the time they took to cover 5, 10 and 20 metres and the time to make an agility test (T court test), with and without a racket. The results showed that the use of the racket negatively impacts the movement ability of the players. Higher level players seem to make specific displacement movements more efficiently with or without the racket, as compared to lower lever players. Results of our findings, apart from being reference values for trainers, inform about the use of the racket for specific mobility in the physical training of WT players.